SYP-5 regulates meiotic thermotolerance in Caenorhabditis elegans. (3rd June 2021) - Liu, Yuanyuan; Zhao, Qiuchen; Nie, Hui; Zhang, Fengguo; Fu, Tingting; Zhang, Zhenguo; Qi, Feifei; Wang, Ruoxi; Zhou, Jun; Gao, Jinmin
Abstract: Meiosis produces the haploid gametes required by all sexually reproducing organisms, occurring in specific temperature ranges in different organisms. However, how meiotic thermotolerance is regulated remains largely unknown. Using the model organism Caenorhabditis elegans, here, we identified the synaptonemal complex (SC) protein SYP-5 as a critical regulator of meiotic thermotolerance. syp-5 -null mutants maintained a high percentage of viable progeny at 20°C but produced significantly fewer viable progeny at 25°C, a permissive temperature in wild-type worms. Cytological analysis of meiotic events in the mutants revealed that while SC assembly and disassembly, as well as DNA double-strand break repair kinetics, were not affected by the elevated temperature, crossover designation, and bivalent formation were significantly affected. More severe homolog segregation errors were also observed at elevated temperature. A temperature switching assay revealed that late meiotic prophase events were not temperature-sensitive and that meiotic defects during pachytene stage were responsible for the reduced viability of syp-5 mutants at the elevated temperature. Moreover, SC polycomplex formation and hexanediol sensitivity analysis suggested that SYP-5 was required for the normal properties of the SC, and charge-interacting elements in SC components were involved in regulating meiotic thermotolerance. Together, these findings provide a novel molecular mechanism for meiotic thermotolerance regulation.